An Acceptance Model for the Adoption of Battery Electric Vehicles in Thailand - Sithanant, Thana; Sukphisal, Burin; Kamales, Nayika (My University, 2024)
The primary objective of this study is to propose a model that will shape the adoption patterns of battery electric vehicles (BEVs) within the consumer demographic of Thailand. BEVs have emerged as a promising avenue for addressing critical environmental concerns, including air pollution, fossil fuel dependency, and climate change. Despite the successful integration of BEVs in various global markets, the penetration in Thailand remains notably limited in contrast to nations such as the United States, China, and Europe, especially Norway. The investigation begins by delineating the fundamental characteristics of BEVs, followed by a meticulous integration of theoretical underpinnings derived from the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Car Technology Acceptance Model (CTAM). These theoretical frameworks serve as a robust foundation for the analysis. In tandem with this theoretical framework, a host of pivotal determinants from multiple BEV adoption reviews is scrutinized, encompassing aspects like pricing structures, regulatory policies implemented by governmental bodies, the accessibility and robustness of charging infrastructures, the dimensions of environmental consciousness, experiential considerations related to driving, household composition, and residential placement. Consequently, these multifarious determinants are synthesized and result in a novel conceptual framework, thereby engendering a nuanced and insightful comprehension of the pivotal drivers that collectively shape the landscape of BEV adoption within Thailand. Further empirical investigations will be undertaken to a more profound awareness of the intricate dynamics that propel the broader integration of BEVs nationwide.
Keywords: Adoption; Battery electric vehicle; CTAM; UTAUT